An integrative descriptive model of ethical decision making - Strong, Kelly C. (Journal of business ethics, 1992)
This paper presents an integrative, descriptive model of ethical decision making, with special attention given to issues of measurement. After building the model, hypotheses are developed from a portion of it. These hypotheses are tested in an exploratory analysis to determine if further research and testing of this model and the measurement instruments it employs are warranted.